Effect of self-adjustable masking noise on open-plan office worker's concentration, task performance and attitudes. (April 2017) - Vassie, Ken; Richardson, Miles
Highlights: Professional open-plan office workers rejected self-adjustable masking noise. This was despite it increasing performance and improving concentration. An important reason for rejection was reduced awareness of nearby conversations. Abstract: The aim of this study was to investigate the attitudes of workers in an open-plan office towards concentration, task performance and co-worker interaction when wearing earphones with masking noise and when not wearing earphones. The earphones with masking noise were evaluated over the course of a working day and the level of the office noise varied between 51 and 59 dBA. The spectrum of the masking noise was brown noise modified by a PC audio controller and earphones (the spectrum of the modified brown noise was substantially different to that of brown masking noise). The participants were instructed to adjust the masking level to be loud enough to mask any offending office sound but not too loud to cause discomfort. The questionnaire based quantitative study ( Study 1, n = 28) indicates that disturbance to concentration and task performance is reduced by modified brown masking noise thereby confirming previous studies. However all the participants in the qualitative study, which involved both open ended questionnaire and focus group interviews, ( Study 2, n = 28 for open ended questionnaire and 12 for focus groups ) identified that they would not use earphones with modified brown masking noise to counteract office noise. An important reason for this is that modified brown masking noise obscured nearby relevant conversations, which participants identified as being crucial to the success of their overall work task. Other participants rejected the brown masking noise delivered through earphones as it caused irritation and discomfort. It is recommended that future studies into the effectiveness of masking noise in open-plan offices should include consideration of the relevance of nearby conversations. Future studies should also consider other types of masking noise and should measure the level and duration of the masking noise. Practitioner Summary: This paper reports on a multi-methods study into the use of self-adjustable masking noise delivered through earphones to counteract the negative effects of noise on open-plan office workers. It was found that self-adjustable masking noise delivered in this way was rejected by all participants.